Reply to the ‘Comment on “Boosting the solar water oxidation performance of a BiVO4 photoanode by crystallographic orientation control”’ by C. Lu and X. Wang, Energy Environ. Sci., 2025, 18, DOI: 10.1039/D4EE02619E - Han, Hyun Soo; Cho, In Sun; Zheng, Xiaolin (Energy and Environmental Science, 2025)
This reply addresses critiques on the feasibility of textured BiVO4 growth and methodological rigor in texture analysis. We provide experimental evidence demonstrating the viability of [001]-textured BiVO4 films on polycrystalline substrates via laser ablation. Comprehensive analysis confirms that crystallographic orientation significantly enhances PEC performance, reinforcing the importance of texture engineering in the development of efficient photoelectrochemical materials.
Keywords: Crystallographic orientation control; Energy; Experimental evidence; Lasers ablations; Performance; Photo-anodes; Polycrystalline substrates; Solar waters; Texture analysis; Water oxidation